2021
DOI: 10.1002/lt.26186
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation in Children with Urea Cycle Disorders: The Importance of Minimizing Waiting Time

Abstract: Liver transplantation (LT) for children with urea cycle disorders (UCDs) is capable of correcting the enzymatic defect and preventing progressive neurologic injury. We describe the characteristics and outcomes of pediatric LT recipients with UCDs. We identified all pediatric (<18 years) LT candidates with UCDs in the United Network for Organ Sharing (UNOS) database (February 2002 to September 2020). Multivariable Cox and logistic regression were used to determine risk factors for graft loss and cognitive delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…According to the data from United Network for Organ Sharing (UNOS) database including 403 patients with urea cycle disorders (46.2% were OTCD) who underwent transplantation, the 1-, 3-, and 5-year graft survival rates were 90.4%, 86.3%, and 85.2%, respectively. Increased mass of the liver graft and male sex are related to decreased risk of graft loss [8]. In Japan, the 1-, 5-, 10-, and 15-year graft survival rates comprised 91.2%, 87.9%, 87.0%, and 79.3% among pediatric patients with metabolic disorders (OTCD, 20.6% of total) as shown by Kasahara et al [18].…”
Section: Clinical Effectmentioning
confidence: 94%
See 1 more Smart Citation
“…According to the data from United Network for Organ Sharing (UNOS) database including 403 patients with urea cycle disorders (46.2% were OTCD) who underwent transplantation, the 1-, 3-, and 5-year graft survival rates were 90.4%, 86.3%, and 85.2%, respectively. Increased mass of the liver graft and male sex are related to decreased risk of graft loss [8]. In Japan, the 1-, 5-, 10-, and 15-year graft survival rates comprised 91.2%, 87.9%, 87.0%, and 79.3% among pediatric patients with metabolic disorders (OTCD, 20.6% of total) as shown by Kasahara et al [18].…”
Section: Clinical Effectmentioning
confidence: 94%
“…Analysis of data on the patients under 18 year subjected to LTx between February 2002 and September 2020, the waiting list time and male sex were associated with long-term risk for a cognitive delay. Minimizing the waiting time is quite important, in order to maintain the patient's cognition capacities at later terms and improve the quality of life [8].…”
Section: Indications For Surgerymentioning
confidence: 99%
“…Liver transplantation has been shown to improve survival outcomes for patients with nonparacetamol-associated acute liver failure and is currently the only known cure for patients with UCDs [39]. The decision to proceed with liver transplantation is complex and requires the involvement of experienced clinicians to guide patient and family decision-making [40]. Considerations include the likelihood of survival and quality of life without transplantation compared with the overall immediate risks as well as the long-term burden and complications of transplantation.…”
Section: Managementmentioning
confidence: 99%
“…Preliminary analyses suggested that in contrast to nitrogen scavenger therapy, liver transplantation, which becomes relevant if intensified conservative management has failed to protect individuals from potentially life‐threatening recurrent HAEs, appeared to be beneficial for the preservation of cognitive functions 19,21 . This was supported by a recent analysis from the United Network for Organs Sharing database, suggesting that early liver transplantation should be considered in individuals with UCDs to prevent progressive neurological injury, 41 and moreover by data from Japan investigating neonatal‐onset and high‐risk individuals with UCDs 42,43 . However, for individuals with a severe phenotype, the life‐long impact of the first HAE on cognitive function cannot be reversed by liver transplantation, 44 while it is effective for preventing individuals from recurrent hyperammonemic attacks and improving long‐term survival 44,45 .…”
Section: Impact Of Diagnostic and Therapeutic Interventions On Health...mentioning
confidence: 99%